Koszty kontrolowane i niekontrolowane w zakładzie ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (Controllable and Uncontrollable Costs in Insurance Companies, 2006)
Insurance companies are financial institutions which have to reach good results and control their financial conditions all time. One of the solutions in making management process better is responsibility accounting with budgeting and separating centres. To control and estimate centres results it is needed costs division on controllable and uncontrollable. In the paper is presented organization structure in insurance company contained such departments as actuarial departments, investments department, marketing and sale department, adjustment of losses department, legal department, accounting department, administration department and personnel department. For all these departments it is divided costs on controllable and uncontrollable.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 40-47